VLSI and Hardware implementations using Modern Machine Learning Methods - Sandeep Saini; Kusum Lata; Sinha, G R (Boca Raton, FL CRC Press, 2022)
This book aims to provide the latest machine learning based methods, algorithms, architectures, and frameworks designed for VLSI design with focus on digital, analog and mixed-signal design techniques, device modeling, physical design, hardware implementation, testability, reconfigurable design, synthesis and verification, and related areas.
index
Keywords: VLSI; Machine Learning